2019
DOI: 10.3389/fmech.2019.00020
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Underlying Causes of a Discrepancy Between Predicted and Measured Energy Use

Abstract: Simulation is commonly utilized as a best practice approach to assess building performance in the building industry. However, the built environment is complex and influenced by a large number of independent and interdependent variables, making it difficult to achieve an accurate representation of real-world building energy in-use. This gives rise to significant discrepancies between simulation results and actual measured energy consumption, termed "the performance gap." The research presented in this paper qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…46 In terms of the magnitude of the performance gap, the Innovate UK BPE and TOP properties seem to be on par with other research. The average performance gap error of 29% in this study compares with research by Van Dronkelaar, 48 which found gaps of AE34%, and a previous review of literature by Van Dronkelaar, 10 which found errors between 16% and 67%.…”
Section: Reflection On Results and Analysissupporting
confidence: 66%
“…46 In terms of the magnitude of the performance gap, the Innovate UK BPE and TOP properties seem to be on par with other research. The average performance gap error of 29% in this study compares with research by Van Dronkelaar, 48 which found gaps of AE34%, and a previous review of literature by Van Dronkelaar, 10 which found errors between 16% and 67%.…”
Section: Reflection On Results and Analysissupporting
confidence: 66%
“…Although reviews focusing on the performance gap of buildings and building certificates are rare, studies on other issues such as the impact of occupant behavior [2,3], climate [4,5,6,7], heating systems [8,9,10,11]are significant.…”
Section: Previous Reviewsmentioning
confidence: 99%
“…Occupant density and/or schedule Discrepancies between actual and assumed occupant density or schedule lead to higher or lower use of IT equipment, lighting and appliances [7,16,[21][22][23]30,35,36,38,39,41,42,47,50,51,57,59,60,65,67,110,111] Use of secondary heating/cooling, such as electric heaters [95] Internal heat load Occupant density and/or schedule Standard occupancy schedules imply high heat gains, which can result in underestimation/ [16,17,75] overestimation of energy use for heating/cooling…”
Section: Category Building Model Ingredient Occupant-related Performamentioning
confidence: 99%